2017
DOI: 10.1021/acs.accounts.7b00203
|View full text |Cite
|
Sign up to set email alerts
|

Heading toward Macromolecular and Nanosized Bioresponsive MRI Probes for Successful Functional Imaging

Abstract: The quest for bioresponsive or smart contrast agents (SCAs) in molecular imaging, in particular magnetic resonance imaging (MRI), is progressively increasing since they allow for the monitoring of essential biological processes on molecular and cellular levels in a dynamic fashion. These are offshoot molecules of common contrast agents that are sensitive to biochemical changes in their environment, capable of reporting on such changes by inducing MRI signal alteration. Various mechanistic approaches and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 57 publications
(122 reference statements)
2
48
0
Order By: Relevance
“…The log K 1 and log K 2 values of L 1 and L 3 are very similar and somewhat lower than those of L 2 and L 4 . This phenomenon can be attributed, at least in part, to the longer propyl linker connecting the nitrogen atom of the macrocycle and the amide group in L 2 and L 4 , which likely results in a lower electron-withdrawing effect of the amide moiety.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The log K 1 and log K 2 values of L 1 and L 3 are very similar and somewhat lower than those of L 2 and L 4 . This phenomenon can be attributed, at least in part, to the longer propyl linker connecting the nitrogen atom of the macrocycle and the amide group in L 2 and L 4 , which likely results in a lower electron-withdrawing effect of the amide moiety.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…Indeed, the first protonation constant determined for DO3A in 0.15 M NaCl is 1.3 log K units lower than that obtained in 0.1 M KCl, which shows that Chart 1. Structures of Paramagnetic Complexes LnL [1][2][3][4] (Ln = Gd, Eu, Yb) Investigated in This Work and Their Analogy to the Ca-Responsive Bis-Macrocyclic Contrast Agents SCA 1,2 6 Na + complex formation is partially responsible for the low protonation constants determined for L 1−4 . The slightly higher log K 1 H values of L 2,4 in comparison to those of L 1,3 might also be explained by the higher stability of the Na + complexes formed by the latter ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the complexity of this process is much greater than initially expected, calling for broad expertise in a multidisciplinary manner through chemistry, physics, biology, and engineering. The goal of this review is not to comprehensively summarize nanoparticulate CAs for MRI that have been reported so far, 26 as there are many reviews available that list the major types of NPs as CAs (Gd 3+ -based T 1 CAs, 11,27 magnetic T 2 CAs, 14,15,28-30 and dual- T 1 / T 2 CAs 9,31 ) or summarize a special application of CAs ( e.g ., bioresponsive CAs, 32-34 and multimodal CAs 24 ). Instead, this review intends to comprehensively discuss the main rules and mechanisms of nanoparticulate CAs, key factors influencing the relaxation of CAs, and innovative strategies to engineer CAs with high relaxivity.…”
Section: Introductionmentioning
confidence: 99%
“…These agents, which are referred to stimulus-responsive or smart contrast agents, are sensitive to specific fluctuations in the local environment, such as pH, biological metal ion concentration or enzymatic activity, and are capable of reporting on such changes by inducing alterations in the MRI signal [119][120][121][122][123][124]. The change in relaxivity of these agents before and after stimulation is the most important factor in evaluating the efficiency of a stimulus-responsive contrast agent [125].…”
Section: Stimulus-responsive Targetingmentioning
confidence: 99%